Amino acid derivatives of natural chlorins as a platform for the creation of targeted photosensitizers in oncology - A. F. Mironov; P. V. Ostroverkhov; S. I. Tikhonov; V. A. Pogorilyy; N. S. Kirin; O. O. Chudakova; A. A. Tsygankov; M. A. Grin (Тонкие химические технологии, 2021)
Objectives. This study aims to obtain the amino acid derivatives of chlorophyll a and bacteriochlorophyll a for the targeted delivery of pigments to tumor foci. This will increase biocompatibility and, as a result, reduce toxic side effects. In addition to photodynamic efficiency, an additional cytotoxic effect is expected for the obtained conjugates of photosensitizers (PSs) with amino acids. This is owing to the participation of the latter in intracellular biochemical processes, including interaction with the components of the glutathione antioxidant system, leading to the vulnerability of tumor cells to oxidative stress.Methods. In this work, we have implemented the optimization of the structure of a highly efficient infrared PS based on O-propyloxim-N-propoxybacteriopurpurinimide (DPBP), absorbing at 800 nm and showing photodynamic efficacy for the treatment of deep-seated and pigmented tumors, by introducing L-lysine, L-arginine, methionine sulfoximine (MSO), and buthionine sulfoximine (BSO) methyl esters. The structure of the obtained compounds was proved by mass spectrometry and nuclear magnetic resonance spectroscopy, and the photoinduced cytotoxicity was studied in vitro on the HeLa cell line.Results. Conjugates of DPBP with amino acids and their derivatives, such as lysine, arginine, MSO, and BSO have been prepared. The chelating ability of DPBP conjugate with lysine was shown, and its Sn(IV) complex was obtained.Conclusions. Biological testing of DPBP with MSO and BSO showed a 5–6-fold increase in photoinduced cytotoxicity compared to the parent DPBP PS. Additionally, a high internalization of pigments by tumor cells was found, and the dark cytotoxicity (in the absence of irradiation) of DPBP-MSO and DPBP-BSO increased fourfold compared to the initial DPBP compound. This can be explained by the participation of methionine derivatives in the biochemical processes of the tumor cell.